Efficient virtual garment fit evaluation infrastructure based on synthetic avatar target customer groups for MtM application - Ernst, Michael; Christophersen, Antje; Böhm, Monika; Botzenhardt, Ulrich (Communications in development and assembling of textile products, 2020)
Customization becomes more and more popular and influences the product development process in apparel industry. In addition to individualized products, the fit of garments is very important for the customization. Numerous tools are used to take the right measurements, to transport individual posture information and to implement these data correctly into a product pattern based on a predefined construction system. Unfortunately, in most cases the mass customization process takes place without a fitting session. Usually fit and design will be checked in the last process step, when the product is already manufactured. Virtual product development is a powerful tool to change this process getting an early fit and design check. By using a test population representing the target group, it is possible to check the sizing and to screen the fit of a product on individual bodies and postures in a short time. In a joint project between the Virtual Lab of Niederrhein University of Applied Sciences and Avalution GmbH, a practical approach for the implementation of a fitting session to a mass customization product development process was developed. The entire process has a three-level structure: First, the avatar population is built up using garment specific body measurements. Connected to a 3D simulation program, an automatic process of determining the made-to-measure (MtM) values, carrying out the MtM grading and the fitting on the selected avatar are initiated. In a special application, the digital try-ons are finally output as images in different physical aspects for evaluation.